Early Modern Narratives of Diu’s Architecture and Space - Grancho, Nuno (Writingplace, 2018)
It is difficult to envision the scope of how early European visitors of places in other parts of the world struggled to describe what they saw after their arrival. At that time, the classificatory arrangements for recounting peoples and cultures were provided by Aristotle or Herodotus. The practice of labelling and illustrating a place with words and images was made along the lines of what could be expected and known from a comparable place at ‘home’, adapting pieces to match the evident reality. This article explores the sixteenth-century spatial descriptions of Diu authored by João de Castro, Gaspar Correa and João de Barros. It seeks to analyse how these observers identified and construed knowledge about difference in the architectural and urban space of Diu and how this related to wider historical-geographical discourses of the time, when there was no clear framework of territories within which cultural artefacts could meaningfully be organized. By approaching the question of histories and stories of Diu – a place profoundly grounded in Portuguese colonial imagery – through the evocations of visual and literary memory and the understanding of the built environment, the article reveals that a crucial field of inquiry about identity and memory in colonial locations in India has gone largely unnoticed by those who construct a sense of the passage of time. Ultimately, the article claims tangible constructions as legible documents of notional constructions and discusses construction processes, materials and critical receptions as evidence of the physical’s reciprocal relationship to the conceptual construction of the East in European culture.